DNA Computing and Molecular Programming 18th International Conference, DNA 18, Aarhus, Denmark, August 14-17, 2012. Proceedings - Stefanovic, Darko; Turberfield, Andrew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 18th International Conference on DNA Computing and Molecular Programming, DNA 18, held in Aarhus, Denmark, in August 2012. The 11 full papers presented were carefully selected from 37 submissions. The papers are organized in topical sections on advancing the engineering and science of biology and chemistry from the point of view of computer science, physics, and mathematics.
Keywords: Computer science; Data structures (Computer science).; Computer software; Computational complexity; Artificial intelligence; Bioinformatics; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Computational Biology/Bioinformatics.; Artificial Intelligence (incl. Robotics).; Data Structures; Discrete Mathematics in Computer Science